Sugarcane (Saccharum sp.) salt tolerance at various developmental levels - GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD; SKALI SENHAJI, Nadia (My University, 2015)
Salt-stress affects plant growth and development at different stages. In this work, we evaluated the level of salinity tolerance of five sugarcane (Saccharum sp.) varieties: CP66-346, CP65-357, CP70-321, CP59-73 and NCo310 by using different NaCl concentrations (0, 17, 34, 68 and 102 mM). This evaluation was based on the in vitro bud emergency, young plants’ survival and growth in hydroponic system, and finally on the aspect and the growth of calli issued from foliar explants. NaCl stress effects result in a reduction of the final bud emergency percentage. At bud emergence stage, varieties CP66-346 and CP59-73 appeared to be the most salt tolerant while NCo310 behaved as the most salt sensitive. Young plants’ survival and growth are also reduced by salinity and at this stage variety CP66-346 seems to be the most tolerant while CP65-357 and CP70- 321 are the most sensitive. Salinity causes calli necrosis and reduces their growth; varieties NCo310 and CP70-321 appeared to be the most salt tolerant while CP65-357 seems to be the most sensitive. These results indicate that the salt tolerance of a variety depends on the stage of development and the level considered. Consequently, salt tolerance of a given cultivar at whole plant level does not guarantee salt tolerance of tissue or cell cultures issued from this cultivar. Bud emergency stage seems to be the most tolerant stage. Variety CP66-346 appeared to be a salt-tolerant variety at both bud emergence and young plants stages.
Keywords: Sugarcane; salt stress; germination; young plant; callus cultures